Preparation method, product and application of composite photo-anode
By adopting bimetal sulfide composite photoanode (ZnMoS3@ZIF-8/BiVO4), the problems of low salt removal rate and COD degradation rate in existing photoelectrochemical desalination technologies are solved, and high-efficiency and low-energy consumption photoelectric desalination and COD degradation effects are achieved.
Patent Information
- Application Number
- CN202411948675.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-27
AI Technical Summary
In the existing photoelectrochemical desalination technology, the salt removal rate and COD degradation rate of the photoelectrode are relatively low, resulting in high cost, high energy consumption and secondary pollution problems.
Bimetal sulfide composite photoanode (ZnMoS3@ZIF-8/BiVO4) is used to load Mo-ZIF-8 on the surface of BiVO4 film and form a composite photoanode through heating reaction, thereby improving the separation and transfer efficiency of photogenerated electron-hole pairs.
An efficient salt removal rate (104.99μg/(cm2·min) and COD degradation rate (91.07%) were achieved, which significantly improved the photoelectric conversion efficiency and photoelectric desalination performance, and desalination was carried out under zero electrical energy consumption.
Smart Images

Figure CN119638016A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a preparation method, product and application of a composite photoanode. Background Art
[0002] The global energy crisis and water shortage are becoming increasingly serious, seriously affecting the sustainable development of society. Water is the source of life and the core element of sustainable social development. The pollution of freshwater resources has further exacerbated the water shortage crisis. The global water shortage and the demand for desalination technology are becoming increasingly urgent. There are currently a variety of desalination technologies, including multi-stage flash evaporation, multi-effect distillation, electrodialysis, etc. These methods generally have the problems of high cost, high energy consumption and secondary pollution. For example, in reverse osmosis technology, the consumption of electricity accounts for 50% of the total cost; while the cost of electricity and heat energy in multi-step flash evaporation and multi-effect distillation accounts for ~77% and ~66% respectively.
[0003] As a clean and sustainable energy source, solar energy has great development potential. Solar-driven photoelectrochemical desalination technology, which combines solar energy with photoelectrochemistry, is an emerging desalination technology that achieves zero-power consumption desalination and becomes an important way to solve the above problems. The core of solar-driven photoelectrochemical desalination technology is the photoelectrode. At present, the photoelectrodes in the existing technology generally have technical problems such as low salt removal rate and COD degradation rate. Summary of the invention
[0004] Based on the above content, the present invention provides a preparation method, product and application of a composite photoanode. The salt removal rate of the composite photoanode of the present invention can reach 104.99μg / (cm 2 ·min), the degradation rate of organic matter COD is as high as 91.07%.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is a method for preparing a composite photoanode, comprising the following steps:
[0007] Dissolving a zinc source and a molybdenum source in solvent 1 to obtain solution A; dissolving 2-methylimidazole in solvent 1 to obtain solution B;
[0008] The solution A and the solution B are mixed and then allowed to stand, centrifuged, and the precipitate obtained by centrifugation is washed and dried to obtain Mo-ZIF-8;
[0009] The Mo-ZIF-8 is dissolved in solvent 2 and mixed evenly, and then the naphthol film solution is added and mixed evenly to obtain a Mo-ZIF-8 mixed solution;
[0010] Mo-ZIF-8 in the Mo-ZIF-8 mixed solution was loaded on BiVO 4 The film surface was Mo-ZIF-8 / BiVO 4 Photoanode;
[0011] Thioacetamide solution was added to the Mo-ZIF-8 / BiVO 4 The surface of the photoanode is heated to react to obtain the composite photoanode (ZnMoS 3 @ZIF-8 / BiVO 4 photoanode).
[0012] The second technical solution of the present invention is a composite photoanode prepared according to the preparation method.
[0013] The third technical solution of the present invention is the application of the composite photoanode in solar-driven photoelectrochemical desalination.
[0014] A fourth technical solution of the present invention is a photoelectrochemical desalination system, using the composite photoanode as the photoanode.
[0015] The present invention discloses the following technical effects:
[0016] The present invention provides a bimetallic sulfide composite photoanode (ZnMoS 3 @ZIF-8 / BiVO 4 The preparation method of the photoanode has readily available raw materials, simple process, and is easy to realize large-scale industrial production.
[0017] The present invention provides a ZnMoS in a bimetallic sulfide composite photoanode. 3 / BiVO 4 The load of ZnMoS can effectively separate and transfer the photogenerated electron-hole pairs at the photoanode, and significantly improve the photoelectric conversion efficiency and photoelectric desalination performance. 3 / BiVO 4 As a photoanode, it achieved 6.01 mA / cm under zero bias condition with light as driving force. 2 The initial photocurrent and 104.99μg / (cm 2 The salt removal rate of pure BVO photoanode was 44.66 μg / (cm 2·min). Using the current desalination system, the composite photoanode of the present invention can reduce the salt concentration of high-concentration brine from 4275ppm to 72ppm in application, and the solar desalination capacity of the photoanode is 0.270μmol / J. The degradation rate of organic COD is as high as 91.07%, and it has good COD degradation ability. The present invention realizes solar-driven photoelectrochemical desalination and COD degradation without consuming electrical energy. The present invention provides feasible and effective technical support for the development of long-term stable and efficient solar-driven photoelectrochemical desalination technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 The composite photoanode (ZnMoS 3 @ZIF-8 / BiVO 4 ) schematic diagram of the preparation process route.
[0020] Figure 2 The SEM, TEM and mapping images of the composite photoanode of the present invention are shown in Figure 1. (a) and (b) are ZnMoS 3 @ZIF-8 / BiVO 4 SEM images of photoanode, (c) and (d) are ZnMoS 3 @ZIF-8 / BiVO 4 TEM image of the photoanode, (e) ZnMoS 3 @ZIF-8 / BiVO 4 Mapping diagram of the photoanode.
[0021] Figure 3 The desalination performance test diagram of the composite photoanode of the present invention; wherein (a) is ZnMoS 3 @ZIF-8 / BiVO 4 Desalination performance curve of photoanode, (b) ZnMoS 3 @ZIF-8 / BiVO 4 Photoelectrochemical desalination performance of the photoanode.
[0022] Figure 4 The COD degradation performance test diagram of the composite photoanode of the present invention; wherein (a) is ZnMoS 3 @ZIF-8 / BiVO 4COD degradation curve of photoanode, (b) ZnMoS 3 @ZIF-8 / BiVO 4 COD degradation rate of the photoanode. DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0024] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0028] Solar-driven photoelectrochemical desalination technology is an emerging technology method that uses solar energy to remove salt from salt water without an external bias. The present invention constructs a bimetallic sulfide composite photoanode that matches the energy level of perovskite ferroelectric (PF) semiconductor materials. The bimetallic sulfide promotes the separation and transfer of photogenerated electron-hole pairs, slowing down the recombination of electrons and holes. The photocurrent and stability of the desalination system are significantly improved. The efficient and stable photoelectrochemical desalination system has the ability to store energy and desalinate salt water, and the efficient COD degradation makes it have broad development prospects and application potential.
[0029] The first aspect of the present invention provides a method for preparing a composite photoanode, comprising the following steps:
[0030] Dissolving a zinc source and a molybdenum source in solvent 1 to obtain solution A; dissolving 2-methylimidazole in solvent 1 to obtain solution B;
[0031] The solution A and the solution B are mixed and then allowed to stand, centrifuged, and the precipitate obtained by centrifugation is washed and dried to obtain Mo-ZIF-8;
[0032] The Mo-ZIF-8 is dissolved in solvent 2 and mixed evenly, and then the naphthol film solution is added and mixed evenly to obtain a Mo-ZIF-8 mixed solution;
[0033] Mo-ZIF-8 in the Mo-ZIF-8 mixed solution was loaded on BiVO 4 The film surface was Mo-ZIF-8 / BiVO 4 Photoanode;
[0034] Thioacetamide solution was added to the Mo-ZIF-8 / BiVO 4 The surface of the photoanode is heated to react to obtain the composite photoanode (ZnMoS 3 @ZIF-8 / BiVO 4 photoanode).
[0035] In a preferred embodiment of the present invention, the zinc source is Zn(NO 3 ) 2 6H 2 O; the molybdenum source is Mo(acac) 2 ; The solvent 1 is a mixed solvent of N,N-dimethylformamide and methanol in a volume ratio of 1:1; the molar ratio of the zinc source to the molybdenum source is (7-8):1; the molar ratio of the zinc source to the 2-methylimidazole is (0.1-0.2):1.
[0036] The present invention does not impose any particular limitation on the amount of solvent 1 used when preparing solution A and solution B. The amount of solvent 1 used is sufficient to fully dissolve the zinc source, the molybdenum source and 2-methylimidazole.
[0037] In a preferred embodiment of the present invention, the standing time is 12 hours.
[0038] In a preferred embodiment of the present invention, the solvent 2 is anhydrous ethanol; the naphthol membrane solution is Nafion D520 with a mass concentration of 95.0%; and the mass volume ratio of the Mo-ZIF-8 to the naphthol membrane solution is 15 mg:30 μL.
[0039] The present invention does not impose any particular limitation on the amount of solvent 2, and the amount of solvent 2 used can be sufficient to fully dissolve Mo-ZIF-8.
[0040] In a preferred embodiment of the present invention, Mo-ZIF-8 is loaded on BiVO by spin coating. 4 Film surface; the Mo-ZIF-8 on the BiVO 4 The loading on the film surface is 1.5-2.0 mg / cm 2 .
[0041] The spin coating method is a conventional technical means in the art and is not the focus of patent protection of the present invention, so it will not be described in detail here.
[0042] In a preferred embodiment of the present invention, the concentration of the thioacetamide solution is 0.1 M; the solvent of the thioacetamide solution is anhydrous ethanol; the thioacetamide in the thioacetamide solution is in the BiVO 4 The loading on the film surface is 0.5-0.9 mg / cm 2 .
[0043] In a preferred embodiment of the present invention, the temperature of the heating reaction is 90° C. and the time is 60 minutes.
[0044] In a preferred embodiment of the present invention, a porous BVO-based film is prepared by electrodeposition and thermal annealing techniques, comprising the following steps:
[0045] 0.02 mol KI was dissolved in 50 mL deionized water and HNO 3 The pH value of the solution was adjusted to about 1.7 to obtain a KI solution; 0.002 mol Bi(NO 3 ) 2 ·5H 2 O was added to the KI solution and stirred, which was marked as solution A; 0.005 mol of p-benzoquinone was dissolved in 20 mL of anhydrous ethanol and stirred continuously, which was called solution B; solution B was added to solution A to form a uniform mixture; then nanostructured BiOI was electrochemically deposited on the surface of the FTO substrate at a potential of -0.1 V (relative to Ag / AgCl); after the deposition was completed, the BiOI film was washed and dried to obtain a thin film; 0.0006 mol of VO(acac) was added to the solution. 2 Dissolved in 3 mL DMSO and coated on the BiOI film; the BiOI film was annealed at 450 °C for 2 h and then cooled to room temperature to obtain BiVO 4 Thin film. BiVO obtained through other channels such as purchase 4 Thin films are also suitable for use with the present invention.
[0046] A second aspect of the present invention provides a composite photoanode prepared according to the preparation method.
[0047] The third aspect of the present invention provides the use of the composite photoanode in solar-driven photoelectrochemical desalination.
[0048] A fourth aspect of the present invention provides a photoelectrochemical desalination system, using the composite photoanode as the photoanode.
[0049] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0050] The reagents used in the examples of the present invention, unless otherwise specified, were of analytical grade; bismuth (III) nitrate pentahydrate (Aladdin, 99.0%), potassium iodide (Aladdin, 99.0%), p-benzoquinone (Macklin, 99.0%), nitric acid (Sinopharm, 65% to 68%), anhydrous ethanol (Macklin, 99.9%), vanadium acetylacetonate (Aladdin, 98%), dimethyl sulfoxide (Macklin, 99.8%), 2-methylimidazole ( Macklin, 98.0%), zinc (II) nitrate hexahydrate (Macklin, 99.0%), molybdenum acetylacetonate (Macklin, 95.0%), methanol (Macklin, 98.0%), N,N-dimethylformamide (Macklin, 99%), thioacetamide (Macklin, 99%), naphthol membrane solution (D520, 95.0%), sodium hydroxide (Macklin, 95.0%), sodium sulfate (Macklin, 99.0%).
[0051] The composite photoanode (ZnMoS 3 @ZIF-8 / BiVO 4 ) is shown in the schematic diagram of the preparation process route Figure 1 As shown, Figure 1 ZMM represents Mo-ZIF-8. The technical solution provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] Step 1, BVO (BiVO 4 ) Preparation of photoanode
[0054] After ultrasonic treatment of a FTO substrate (3.0 cm × 3.0 cm) in a mixture of acetone, ethanol, and deionized water (volume ratio 1:1:1) for 30 min, the FTO was cleaned with deionized water and placed in anhydrous ethanol for later use. First, 0.02 mol KI was dissolved in 50 mL deionized water and HNO 3 Solution Adjust the pH of the KI solution to about 1.7. Add 0.002 mol Bi(NO 3 ) 2 ·5H 2 O was added to the KI solution and stirred, which was marked as solution A. 0.005 mol of p-benzoquinone was dissolved in 20 mL of anhydrous ethanol and stirred continuously as solution B. Solution B was added to solution A to form a uniform mixture. Secondly, nanostructured BiOI was electrochemically deposited on the surface of the FTO substrate at a potential of -0.1 V (relative to Ag / AgCl). After the deposition was completed, the formed BiOI film was rinsed three times with deionized water and anhydrous ethanol, respectively, and then dried at 80°C. Finally, 0.0006 mol VO(acac) 2 Dissolved in 3 mL DMSO and coated on the BiOI film. Annealed the BiOI film at 450 °C for 2 h and then cooled to room temperature. Washed the sample with 0.1 M NaOH solution to obtain a porous BVO film (ie, BVO photoanode).
[0055] Step 2, Mo-ZIF-8 / BiVO 4 Preparation of photoanode
[0056] Zinc nitrate (Zn(NO 3 ) 2 6H 2 O, 0.587g) and molybdenum acetylacetonate (Mo(acac) 2 , 0.088 g) was uniformly dissolved in a mixed solution of N,N-dimethylformamide-methanol (v / v=1:1, 20 mL) and stirred continuously for 10 min, which was recorded as solution A. Weigh 2-methylimidazole (C 4 H 6 N 2 , 1.298g) was uniformly dissolved in a mixed solution of N,N-dimethylformamide-methanol (v / v=1:1, 20mL) and stirred continuously for 10min, which was recorded as solution B. Then, solution A was transferred to solution B and mixed thoroughly, stirred continuously for 10min, and allowed to stand at room temperature for 12h. The obtained white suspension was centrifuged at 8000rpm, and the precipitate obtained by centrifugation was washed 3 times with anhydrous ethanol and deionized water respectively. Finally, it was dried in a vacuum oven at 80℃ for 8 hours to obtain a white powder (named Mo-ZIF-8) for standby use.
[0057] Weigh 15 mg of Mo-ZIF-8 sample and add it to 470 μL of anhydrous ethanol. Ultrasonicate for 30 min to obtain a Mo-ZIF-8 solution. Add 30 μL of naphthol membrane solution (D520) to the Mo-ZIF-8 solution and ultrasonicate for 60 min to obtain a white Mo-ZIF-8 mixed solution. Spin coat the Mo-ZIF-8 mixed solution onto a 3 cm × 3 cm BiVO 4 The photoanode surface was dried in an oven at 60 °C for 12 h to obtain Mo-ZIF-8 / BiVO 4 Photoanode (named ZMB).
[0058] (3) ZnMoS 3 @ZIF-8 / BiVO 4 Preparation of photoanode
[0059] 0.05 g of thioacetamide (C 2 H 5 NS) was uniformly dissolved in 6.5 mL of anhydrous ethanol and ultrasonicated for 10 min to obtain a 0.1 M thioacetamide solution. A 3 cm × 3 cm ZMB photoanode was placed in a 90 ° C oven, and 1.0 mL of thioacetamide (0.1 M) solution was added dropwise to the surface of the ZMB photoanode and kept at 90 ° C for 60 min. ZnMoS 3 @ZIF-8 / BiVO 4 Photoanode (named Mo-ZSB).
[0060] Figure 2 The SEM, TEM and mapping images of the composite photoanode prepared in Example 1 of the present invention; wherein (a) and (b) are ZnMoS 3 @ZIF-8 / BiVO 4 SEM images of photoanode, (c) and (d) are ZnMoS 3 @ZIF-8 / BiVO 4 TEM image of the photoanode, (e) ZnMoS 3 @ZIF-8 / BiVO 4 Photoanode mapping diagram. Figure 2 In (a) and (b), it can be seen that ZnMoS 3 @ZIF-8 is evenly distributed in BiVO 4 Surface, by Figure 2 In (c) and (d), it can be seen that in ZnMoS 3 @ZIF-8 / BiVO 4 BiVO also appears in the material 4 The 112 crystal plane and ZnMoS 3 @Diffraction of ZIF-8; Figure 2 (e) is ZnMoS 3 @ZIF-8 / BiVO 4 Photoanode mapping diagram, showing ZnMoS 3 @ZIF-8 / BiVO 4 Successful preparation.
[0061] Figure 3 The desalination performance test diagram of the composite photoanode prepared in Example 1 of the present invention (the test method adopts the photoelectrochemical test method); wherein (a) is ZnMoS 3 @ZIF-8 / BiVO 4 Desalination performance curve of photoanode, (b) ZnMoS 3 @ZIF-8 / BiVO 4 Photoelectrochemical desalination performance of the photoanode. Figure 3 It can be seen that ZnMoS 3 @ZIF-8 / BiVO 4 The photoelectrochemical desalination performance of the photoanode is 104.99 μg / (cm 2 ·min), and maintained good stability in five cycle tests.
[0062] Figure 4 The COD degradation performance test diagram of the composite photoanode prepared in Example 1 of the present invention (the test method refers to GB / T5750.7-2023); wherein (a) is ZnMoS 3 @ZIF-8 / BiVO 4 COD degradation curve of photoanode, (b) ZnMoS 3 @ZIF-8 / BiVO 4 The COD degradation rate of the photoanode is given by Figure 4 It can be seen that ZnMoS 3 @ZIF-8 / BiVO 4 The COD degradation rate of the photoanode was 91.07%, and it maintained good stability during five cycle tests.
[0063] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a composite photoanode, characterized in that: The following steps are involved: Dissolving a zinc source and a molybdenum source in solvent 1 to obtain solution A; dissolving 2-methylimidazole in solvent 1 to obtain solution B; The solution A and the solution B are mixed and then allowed to stand, centrifuged, and the precipitate obtained by centrifugation is washed and dried to obtain Mo-ZIF-8; The Mo-ZIF-8 is dissolved in solvent 2 and mixed evenly, and then the naphthol film solution is added and mixed evenly to obtain a Mo-ZIF-8 mixed solution; The Mo-ZIF-8 in the Mo-ZIF-8 mixed solution is loaded on the surface of the BiVO4 film to obtain a Mo-ZIF-8 / BiVO4 photoanode; The thioacetamide solution is added to the surface of the Mo-ZIF-8 / BiVO4 photoanode for heating reaction to obtain the composite photoanode.
2. The method for preparing the composite photoanode according to claim 1, characterized in that: The zinc source is Zn(NO3)2·6H2O; the molybdenum source is Mo(acac)2; the solvent 1 is a mixed solvent of N,N-dimethylformamide and methanol in a volume ratio of 1:1; the molar ratio of the zinc source to the molybdenum source is (7-8):1; the molar ratio of the zinc source to the 2-methylimidazole is (0.1-0.2):
1.
3. The method for preparing the composite photoanode according to claim 1, characterized in that: The standing time is 12 hours.
4. The method for preparing the composite photoanode according to claim 1, characterized in that: The solvent 2 is anhydrous ethanol; the naphthol membrane solution is Nafion D520 with a mass concentration of 95.0%; the mass volume ratio of the Mo-ZIF-8 to the naphthol membrane solution is 15 mg:30 μL.
5. The method for preparing the composite photoanode according to claim 1, characterized in that: Mo-ZIF-8 was loaded on the surface of BiVO4 film by spin coating; the loading amount of Mo-ZIF-8 on the surface of BiVO4 film was 1.5-2.0 mg / cm 2 .
6. The method for preparing the composite photoanode according to claim 1, characterized in that: The concentration of the thioacetamide solution is 0.1M; the solvent of the thioacetamide solution is anhydrous ethanol; The loading amount of thioacetamide in the thioacetamide solution on the surface of the BiVO4 film is 0.5-0.9 mg / cm 2 .
7. The method for preparing a composite photoanode according to claim 1, characterized in that: The temperature of the heating reaction is 90° C. and the time is 60 min.
8. The composite photoanode prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the composite photoanode as claimed in claim 8 in solar-driven photoelectrochemical desalination.
10. A photoelectrochemical desalination system, characterized in that: The composite photoanode according to claim 8 is used as the photoanode.
Citation Information
Patent Citations
S-FeOOH / bismuth vanadate composite photo-node and preparation method thereof
CN113235124A
Preparation method and application of ZIF-8-derived ZnO / BiVO4 heterojunction compound
CN115845832A
Ag2MoO4 / BiVO4 photo-anode and preparation method and application thereof
CN116947168A
Photocatalyst composite powder and its manufacturing method
JP2004105957A
Carbon dioxide reduction device
KR101839819B1